Six new species of Diacyclops (Copepoda: Cyclopoida) from Australia - Karanovic, Tomislav (Zootaxa, 2024)
Nine species and one subspecies of the freshwater copepod genus Diacyclops Kiefer, 1927 have been reported so far from Australia. Two of them are nearly cosmopolitan and frequently found in disturbed surface waters, one is endemic to eastern Australia and found predominantly in springs, while all others are endemic to the Pilbara region of Western Australia and found only in subterranean waters. Here I describe another six endemics: one from a spring in South Australia (D. leijsi sp. nov.), one from two caves in the south-western corner of Western Australia (D. eberhardi sp. nov.), one from several bores in the Pilbara region of Western Australia (D. ballaballensis sp. nov.), and three from several bores in New South Wales (D. hancocki sp. nov., D. tomlinsonae sp. nov., and D. huntervalleyensis sp. nov.). All six new species are easily distinguishable from each other by a unique shape and armature of the caudal rami and a different armature formula of the swimming legs. All, except one pair, also have a different armature formula of the antenna. Interestingly, all nine Western Australian endemics have a 12-segmented antennula (and other characters of the alticola-group), while the four endemics from eastern Australia have this appendage further reduced. Because of this, and previous molecular work that suggested a polyphyly of the Western Australian species, I performed a cladistic analysis of all 16 Australian taxa based on 21 morphological characters. As with many groups that are dominated by subterranean species, the resulting cladograms suggest numerous homoplasies. The group of species from eastern Australia is certainly polyphyletic, while the Western Australian group appears to be paraphyletic. A key to all Australian species is also included.